Implementation of the Integrated Waste Management Site (TPST) Program: Pelaksanaan Program Tempat Pengelolaan Sampah Terpadu (TPST) - Ali, Mochammad Fachrizal; Umar, Ahmad Riyadh (Indonesian Journal of Public Policy Review, 2024)
The study analyzed the implementation of waste management at BUMDes Bhirawa in the Mekarsari Integrated Waste Treatment Site (TPST) in Kureksari Village using a qualitative descriptive method. Data was gathered from interviews, observation, documentation, and literature studies, and the informants included the Bhirawa BUMDes Secretary, the Kureksari Village Government, and the TPST users. The research revealed four variables: communication, data source, dispositions, and bureaucratic structure. The results emphasized the importance of effective communication, data management, employee attitudes, and bureaucratic structure for successful waste management programs Highlight : Communication: The study emphasizes the importance of effective communication in waste management programs. Communication was carried out through electronic media, socialization, and training. Data Management: The study highlights the significance of data management in waste management programs. The data source was sufficient, with a special budget for employee salaries and TPST maintenance. Employee Attitudes and Bureaucratic Structure: The study suggests that employee attitudes and bureaucratic structure play a crucial role in successful waste management programs. The results revealed that employees were responsible for their duties, and the bureaucratic structure had clear standard operating procedures and a well-executed division of responsibilities. Keywords: Waste Management, BUMDes Bhirawa, Mekarsari Integrated Waste Treatment Site (TPST), Kureksari Village, Qualitative Descriptive Method